Rebooting Ecumenism - New Paradigms for the 21st Century (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Today’s world is very different to that of the ‘golden age’ of ecumenism, soon after World War II, when churches and their theologians around the world embraced the idea of ecumenism with drive and enthusiasm. In those fraught times, unity appeared as an existential, post-traumatic necessity, and it was sought in the genuine spirit of post-war humility. Our current times, once again, compel us to do the same. With various emerging divisive borderlines in modern societies and the weight of a new ongoing cold war, tensions have increased to perilous levels, even giving rise to an internecine war in Europe, while the situation in the Middle East becomes ever more precarious. This is why, in the face of today’s conflicts and divisions, we are called on once again to make ecumenism a priority for all religious denominations worldwide. The concept guiding the papers in this Special Issue is a renewed focus on new potential paradigms, or indeed old models worth revisiting, that would ensure a more fruitful and dynamic ecumenical fellowship for the future. Therefore, this Special Issue has sought to explore novel models of perceiving or conceiving ecumenism, from historical to contemporary examples, from theological to ecclesiological or pastoral designs, and from spirituality to methodology. The materials included here come from a variety of Christian traditions – though mostly from the Orthodox context – and create a hopeful picture for the future, bringing new and creative perspectives in support of a fundamental, inescapable ecumenical core of Christian theology.